Student’s Speaking Anxiety and Motivation in EFL Learning Process at Vocational High Schools in North Bintan - Kharisma Dewi, Yoffie (Tadris Pendidikan Bahasa Inggris IAIN Langsa, 2023)
The research aims at exploring the relationship between speaking anxiety and motivation among vocational high school students in EFL learning in Bintan Islands. In conducting this research, the method used is descriptive analysis. There are 60 samples taken from four vocational high schools with 15 samples from each school. Those are SMKN 1 Bintan Utara, SMKN 1 Seri Kuala Lobam, SMK Perkapalan, and SMK Muhammadiyah. The data collected were in the form of questionnaire and interview. The results of this research found that there are some factors that influence students’ EFL learning process such as anxiety about mispronouncing, making mistakes, and regarding teacher interruption for mistake correction, the lack of vocabulary, and the less attractive and interactive teaching style in the classroom. Those factors cause the low motivational issue in speaking English matters.